Training on watershed conservation and water filter making as part of the Adiwiyata School program assistance at SMK Swasta Gelora Jaya Nusantara Medan - Sri Wahyuni; Martalena Br. S. Kembaren; Noverita Sprinse Vinolina (Outline Publisher, 2024)
One of the activities that schools must do to become Adiwiyata schools is to carry out water and water source conservation activities. SMK Gelora Jaya Nurantara (GJN) is committed to becoming one of the Adiwiyara schools and with the DRTPM 2024 grant, Inkes Sumut can help SMK GJN. The method used is training and practice of watershed conservation. The activity was carried out in August 2024 with 35 participants consisting of students and teachers of the Adiwiyata School team. The activity was carried out well and achieved the target. The school was given 50 seeds of keladi plants which were used as plants for watershed conservation and have all been planted. 2 sets of water filters were also given to the school as a means of filtering river water so that it can be used for daily needs at the school this is a form of technology application in this community service activity. Then there are changes in knowledge and skills before and after training in all training participants. All activities were carried out properly, enthusiastically and the school also received and benefited from this community service activity. In the future, it is hoped that SMK GJN can perfect all preparations towards Adiwiyata school.